THE PSYCHOLOGICAL CONTRACT: : THE CORE STAGE OF ORGANIZATIONAL SOCIALIZATION OF UNIVERSITY STUDENTS - Fernández Reina, Mariana (Revista Arbitrada Formación Gerencial, 2024)
The objective of this article is to reflect on an aspect of organizational behavior, such as the psychological contract that is generated between university students and the Núcleo Costa Oriental del Lago of the Universidad del Zulia as an educational organization. It describes the stages of the socialization process followed by the new students at the Nucleus, analyzing the characteristics of this population that affect in different ways this core process, which affects their successful academic performance, especially those related to the stage of the psychological contract as part of the socialization process. Finally, some final reflections on the subject are established, among which the importance of the psychological contract in the establishment of a harmonious and nurturing organizational climate in the university context is highlighted.